PENGARUH KONSENTRASI ATONIK TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (ALLIUM CEPA VAR. AGGREGATUM L.) VARIETAS LEMBAH PALU - Azwar, Azwar; Pasigai, Muhammad Anshar; Lasmini, Sri Anjar (AGROTEKBIS, 2018)
The study aims to determine the concentration of hormones grown atonic to the growth and yield varieties of Palu Valley. The research was conducted in Bulupontu Jaya Sub-Village, Sidera Village, Biromaru Sub-district, Sigi Regency, Central Sulawesi Province. This study used Randomized Block Design consisting of 4 treatment levels: A1 = 0.5 ml / L water, A2 = 1 ml / L water, A3 = 1.5 ml / L water, and A4 = 2, 0 ml / L water.All treatments were repeated 3 (three) times, so there were 4 treatments each time 3 replicates = 12 experimental units.The results showed that the atonic concentration of 2.0 ml / L water had significant effect on the growth and the best onion crop yields indicated by the average plant height of 23.17 cm,average number of leaves 24.40 strands, number of tiller 5.67 fruit, total dry weight of crop 1.70 gram, number of tubers per hump 5.40 fruit, tuber weight per hill 25.48 gram, weight per bulb 3.35 gram and tuber yield per hectare 3.77 ton.ha-1.